Hubungan Kecerdasan Emosional dan Minat Belajar terhadap Pemahaman Bencana Alam pada Siswa Sekolah Dasar - Azizah, Khusnaini; Wibowo, Firmanul Catur; Rosita, Tita (Universitas Muhammadiyah Metro, 2024)
This research aims to determine the relationship between emotional intelligence, interest in learning, and elementary school students' understanding of natural disasters in Labuan District. The research was conducted at five public schools in Labuan District, namely SDN Teluk 1, SDN Teluk 2, SDN Teluk 3, SDN Labuan 1, and SDN Cigondang 2, with a sample size of 300 students. This research uses a quantitative approach with survey methods. Hypothesis testing is carried out using multiple regression tests. The research results concluded that: 1) There is a significant relationship between emotional intelligence (X1) and understanding of natural disasters (Y) of elementary school students in Labuan District. The Sig value can prove this. = 0.000 < 0.05 and t0 = 7.269; 2) There is a significant relationship between interest in learning (X2) and understanding of natural disasters (Y) of elementary school students in Labuan District. The Sig value can prove this. = 0.000 < 0.05 and t0 = 11.202; 3) There is a significant relationship between emotional intelligence (X1) and interest in learning (X2), together with the understanding of natural disasters (Y) of elementary school students in Labuan District. The Sig value can prove this. = 0.000 < 0.05 and Fo = 551.907.